ҚУБЛА-ШЫҒЫС ҮСТИРТ АЙМАҒЫНДАҒЫ ТАРИЙХЫЙ ЖЕР-СУЎ АТАМАЛАРЫ ҲАҚҚЫНДА - Қанаатов, Е.Е.; Шамшаддинова, С.С. (FAN va JAMIYAT, 2023)
The article talks about the historical toponyms of the South-Eastern Ustyurt. South-Eastern Ustyurt is a rich region with historical objects. The names of land and water in this region reveal the secret of history. The authors explore the etymology, lexical and semantic meaning of the names of land and water in this region, and also express their opinion on some toponyms. The authors also divide the toponyms of the South-Eastern Ustyurt into 3 types depending on their origin, lexical and semantic features.